Simulasi Deteksi Marka Jalan Menggunakan Canny Edge Detection untuk Navigasi Kendaraan Otonom - Febrian Akbara; Ii Munadhif; Mohammad Abu Jami'in; Ryan Yudha Adhitya; Imam Sutrisno (Journal of Applied Smart Electrical Network and Systems, 2025)
This study develops an automatic steering control system based on image processing using the Canny Edge Detection method. The system is implemented on a small-scale autonomous vehicle prototype, utilizing Raspberry Pi 5 as the main processor and a Pi Camera as the visual sensor. Video frames are processed through several stages, including color conversion, Grayscale, Gaussian blur, Edge Detection, Region of Interest (RoI), and lane center estimation. The results show an average lane detection accuracy of 96% with responsive steering control, indicating the system's potential for lightweight autonomous vehicle navigation.